Archaeology: Old World, B.C. - Science Service (New York Doubleday, 1971)
A general discussion of archaeology with emphasis on Old World sites and the use of scientific methods in excavations.
UPSA-1799g donated by Eliza Romualdez-Valtos
Keywords: Archaeology -- Juvenile literature; Archaeology